2013
DOI: 10.1111/pbr.12063
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of selection at CIMMYT's main maize breeding sites in Mexico for performance at sites in Africa and vice versa

Abstract: The exchange of elite breeding materials across regions is an important way in which multinational maize breeding programmes access new genetic variation, improve efficiency and reduce costs. Our objectives were to examine whether CIMMYT's breeding programmes for tropical and subtropical environments in Mexico and Eastern and Southern Africa (ESA) can effectively share materials. Sets of selected and unselected lines were evaluated for per se and testcross performance in multiple environments in Mexico and ESA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…This can translate into adaptation even to regions where the cultivar was not originally tested, because similar production environments can occur across regions and even continents. For example, Kebede et al (2013) have shown that maize variety trials conducted in subtropical areas of Mexico and southern Africa yield highly correlated results. The similarity of production environments across vast regions has led to the selection of varieties exhibiting very broad adaptation to a range of climatic conditions.…”
Section: Elements Of Climate-adaptive Breeding and Seed Systemsmentioning
confidence: 99%
“…This can translate into adaptation even to regions where the cultivar was not originally tested, because similar production environments can occur across regions and even continents. For example, Kebede et al (2013) have shown that maize variety trials conducted in subtropical areas of Mexico and southern Africa yield highly correlated results. The similarity of production environments across vast regions has led to the selection of varieties exhibiting very broad adaptation to a range of climatic conditions.…”
Section: Elements Of Climate-adaptive Breeding and Seed Systemsmentioning
confidence: 99%
“…The development of new maize germplasm able to tolerate drought, high temperatures, N deficiency, and biotic stresses is crucial if productivity in maize‐based farming systems is to be sustained or increased in tropical lowlands in Latin America. Germplasm developed in Latin America is equally likely to perform well in similar agroecological environments prone to drought and high temperatures in southern and eastern Africa and southern Asia (Kebede et al, 2013). The objective of this study was to evaluate elite lines currently available in CIMMYT's lowland tropical breeding program in Latin America under multiple abiotic stresses and identify germplasm for tolerance to drought, N deficiency, and HTDS.…”
mentioning
confidence: 99%
“…Entonces la selección en ambos ambientes traerá cambios en el mismo sentido cuando la población sea llevada al otro ambiente, ocurriendo lo contrario sólo para el peso de la mazorca, que es el carácter que más impacta al productor. Excepto para rendimiento de grano, los resultados son similares a los de Kebede et al, (2013), que estudiando el comportamiento de líneas endogámicas y sus cruzas en México y el este y sur de África encontraron correlaciones de 0.72 o superiores para rendimiento de grano, días a floración femenina y altura de planta, concluyendo que puede intercambiarse material genético entre ambos ambientes.…”
Section: Cuadro 1 Valores Promedio Para Las Variables Evaluadasunclassified
“…La selección por peso de mazorca en ambiente de humedad residual se traducirá en una merma de poco más de medio punto porcentual por cada ciclo de selección al llevar a la población al ambiente de secano, en parte por el muy bajo valor de heredabilidad en el ambiente de selección, pero hay que tomar en cuenta que el ambiente de secano puede considerarse un ambiente de baja productividad y al respecto Atlin et al, (2001) señalan que programas formales de mejoramiento genético han sido exitosos en desarrollar variedades de alto rendimiento llevando múltiples evaluaciones a través de ambientes favorables, pero menos exitosos en desarrollar materiales que superen a los maíces locales en ambientes marginales. Windhausen et al, (2013) coinciden en lo anterior cuando dicen que la división en sub regiones es innecesaria solo cuando hay poca diferencia entre ellas, lo que no aplica en este trabajo. También Banziger et al, (1997) concluyeron que la selección en ambiente de alto nitrógeno para comportamiento en bajo nitrógeno traerá una reducción en rendimiento cuando la deficiencia excede 43 %.…”
Section: Cuadro 1 Valores Promedio Para Las Variables Evaluadasunclassified
See 1 more Smart Citation